THE EFFECTS OF ENTERPRISE ACCOUNTING POLICIES REGARDING DEPRECIATIONS UPON THE RESULTS AND CORPORATE TAXES - Sorin, Grigorescu; Dorina, Luţă (Strategii Manageriale, 2013)
Depreciation and net results define the self-financing ability of an enterprise and any change in depreciations generates reverse effects upon a corporate tax. That is why the measurement and depreciation system of assets must be correlated with capital maintenance. In the event of depreciation, accounting policies may envisage the choice of one of the depreciation methods, for example straight-line, accelerated or degressive methods of depreciation. Choosing a method of depreciation involves an accounting option. The present article includes a comparative approach of depreciation methods and their implications upon the results and profit taxes, comprising own perspectives and opening new research prospects. The question can be “Which method is the best to use?”. The answer depends on enterprise objectives, on the “aggressiveness” used when it wants to approach fiscal management.